La motivación en el proceso de enseñanza – aprendizaje de los alumnos del tercer año de educación básica de la Escuela Ernesto Noboa y Caamaño del recinto San Jacinto, parroquia Zapotal, cantón Ventanas, del año lectivo 2010 – 2011 - Bustamante Barragán, Gabriela María (2011)
This Project of Thesis was a very pleasing challenge for us because it took us to investigate and to investigate on such an important topic in our means as it is ―The motivation‖, knowing that of her all good learning depends, because if we are our desmotivados self-esteem it would suffer largely and it would impede that you interioricen new knowledge, for this cause decides to visit a well-known school of our county for this way to be able to help those who are going by this problem type. When interacting in the problem we learned knowing of the reality in that he/she lives today's student, tomorrow's professional, and many people in the whole world. that the motivation lack in the teaching process-learning hinders and it prevents that the learning is significant and functional. By means of the I dialogue with teachers, parents and students we feel satisfied when listening to them and to see them motivated with the topic, giving their opinions and mentioning their lived experiences of what was good us our Project of Thesis that was an entire success to argue. We also thank to our professors who made emphasis in the importance that has being interested in the students, and that for their offered knowledge we could execute in our way Project of Thesis.